1997
DOI: 10.1161/01.cir.96.12.4226
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Serum Cholesterol in Postmenopausal Women With Previous Myocardial Infarction and Cholesterol Malabsorption Induced by Dietary Sitostanol Ester Margarine

Abstract: Dietary use of sitostanol ester margarine normalizes LDL cholesterol in about one third of women with previous myocardial infarction, especially in those with high baseline absorption and low synthesis of cholesterol, and in combination with statins reduces the needed drug dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
141
1
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(161 citation statements)
references
References 26 publications
15
141
1
4
Order By: Relevance
“…This result is similar to those of earlier studies, in which plant stanol esters (2-3 g/day of plant stanols) have reduced LDL-C by 9-15% (Vanhanen et al, 1993;Gylling and Miettinen, 1994;Gylling et al, 1995Gylling et al, , 1997Gylling et al, , 1999Miettinen et al, 1995;Hallikainen and Uusitupa, 1999;Hallikainen et al, 2000a;Mensink et al, 2002). Our result also confirms the fact that plant stanol ester does not affect serum HDL-C or TG.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is similar to those of earlier studies, in which plant stanol esters (2-3 g/day of plant stanols) have reduced LDL-C by 9-15% (Vanhanen et al, 1993;Gylling and Miettinen, 1994;Gylling et al, 1995Gylling et al, , 1997Gylling et al, , 1999Miettinen et al, 1995;Hallikainen and Uusitupa, 1999;Hallikainen et al, 2000a;Mensink et al, 2002). Our result also confirms the fact that plant stanol ester does not affect serum HDL-C or TG.…”
Section: Discussionsupporting
confidence: 93%
“…Thus one can with confidence claim that the reduction in serum lipids in the stanol group was almost certainly owing to the plant stanols. The daily intake of plant stanol was 2 g, which was, on the basis of the earlier studies (Vanhanen et al, 1993;Gylling and Miettinen, 1994;Gylling et al, 1995Gylling et al, , 1997Gylling et al, , 1999Miettinen et al, 1995;Hallikainen and Uusitupa, 1999;Hallikainen et al, 2000a;Mensink et al, 2002), estimated to be adequate.The daily dose of the cheese product was taken in one or two portions with main meals. It has been reported that plant stanols, either consumed once a day or divided between the meals, resulted in a similar decrease in serum lipids .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Table 3 shows the results of studies investigating the differences in effects that plant sterols or stanols have on lipid levels in statin users and non-statin users. All studies have demonstrated that if plant sterols or stanols are added to a statin, the effect on cholesterol reduction is similar (40,43) or even higher (44) compared with that observed with the use of the plant sterols or stanols alone.…”
Section: Mechanism Of Supporting Statin Therapymentioning
confidence: 99%